STATE-LOCAL RELATIONS AND INTERNALLY GENERATED REVENUE IN NIGERIA: HOW EFFECTIVE IS THE COLLABORATION - Randy Oyovwevotu Sakpere (Galaxy International Interdisciplinary Research Journal, 2021)
T State-local relations in Nigeria is intended to promote good governance in Nigeria through improving internally generated revenue, however, the nature and practice of the relationship currently, is a major obstacle to good governance. This paper assessed effect of state-local relations on internally generated revenue. The study adopted survey design that drew data using structured questionnaire and oral interviews from Ministry, Department and Agencies (MDAs) of state and local governments saddled with revenue management. Data were generated from 387 respondents, and data collected were subjected to statistical analysis such as mean and regression. Secondary data was obtained from National Bureau of Statistics (NBS). The result showed that payment of taxes through banks and creation of awareness and sensitization of the populace on the tax payment were strategies employed for improving internally generated revenue. The result also revealed that state-local relations have fairly improved internally generated revenue in the country. The result further state-local relations have not improved administrative efficiency, and transparency and accountability in the management of internally generated revenue. The study concluded that state-local relation has not effectively improved internally generated revenue in Nigeria.